Ag nanoparticle surface-plasmon-resonance-enhanced electroluminescence from semipolar n-ZnO/p-GaN heterojunction light-emitting diodes. (30th August 2018) - Wang, Xiao; Bai, Lihua; Zhang, Heng; Su, Xi; Wu, Hao; Liu, Chang
Abstract: Ag nanoparticles (NPs) were used to demonstrate the surface-plasmon-resonance (SPR)-enhanced electroluminescence (EL) from semipolar n-ZnO/p-GaN heterojunction light-emitting diodes (LEDs). Ag NPs were synthesized with an average diameter of 30 nm, which was well matched to the optimal calculation result obtained by the finite difference time domain (FDTD) method. The photoluminescence intensities from the top excitation of GaN and ZnO were 70 and 40% enhanced by coupling Ag NPs, respectively. The EL intensity was increased 20% by lighting the semipolar n-ZnO/p-GaN heterojunction LEDs coupled with Ag NPs.